2020
DOI: 10.3390/ijerph17010346
|View full text |Cite
|
Sign up to set email alerts
|

Play as a Method to Reduce Overweight and Obesity in Children: An RCT

Abstract: Background: Overweight and obesity are the result of a complex interaction between genetic and environmental factors, which begins prenatally. Aim: To analyse an intervention based on play as a means of improving the body composition of children who are overweight or obese. Methods: The Kids-Play study is a randomized clinical trial (RCT) consisting of 49 children aged 8–12 years on a nine-month intervention programme based on physical activity, play and nutritional advice. Controls had another 49 children, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In this study, we found that children who are not obese spent more time per week to actively participate in play activities than children who are obese. This finding is similar to Sánchez-López et al [13] and Janssen [21] studies in which they found similar results and have gone to further recommend that spending more time actively participating in play among children might be an effective means to fight childhood overweight and obesity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, we found that children who are not obese spent more time per week to actively participate in play activities than children who are obese. This finding is similar to Sánchez-López et al [13] and Janssen [21] studies in which they found similar results and have gone to further recommend that spending more time actively participating in play among children might be an effective means to fight childhood overweight and obesity.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the transition from childhood to adolescence appears to be a period during which active participation in play declines, with the end of primary school (10-11 years) being a critical period [12]. Sánchez-López et al [13] emphasized that this decline in active participation in play in these children is associated with increase in their BMI. This is because, children expend high calories of energy through active participation in play [14].…”
Section: Introductionmentioning
confidence: 99%
“…An important prerequisite for the validity of the DID method is the convergence hypothesis ( Bogadóttir, 2020 ; Khan et al, 2020 ; Sánchez-López et al, 2020 ). In our study, this means that, if the raw milk purchase guide price policy was not implemented, the price trend in the province or municipality of the experimental group should have been equal to that of the control group.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear that we need continued research and development of cost‐effective behavioral and systems‐level interventions to curb obesity and promote more successful educational outcomes (Davies et al, 2007). Some nascent approaches appear to be promising, including implementation of nutrition policies in schools (e.g., alternatives to food‐based rewards/celebrations; Ickovics et al, 2019), promotion of healthy school food environments (Teo et al, 2019), classroom‐based lifestyle interventions (Hsiang et al, 2020; Salam et al, 2020), school‐based nutritional education programs (Hawkins et al, 2020), summer and after‐school weight management programs (Mabli et al, 2020; Reesor et al, 2018), as well as initiatives aimed at reducing sedentary behavior and screen time (Goldthorpe et al, 2020), with a synchronized focus on increased physical activity through after‐school clubs, class physical activity breaks (Jones et al, 2020; Santina et al, 2020; Yuksel et al, 2020), and play‐based interventions (Sanchez‐Lopez et al, 2020). Moreover, an important component of any intervention strategy is to incentivize decision‐makers to advocate for increased funding as a way to implement more large‐scale social policy changes to educate and train the next generation of school‐based health practitioners (e.g., occupational therapists) who will undoubtedly have a significant impact on child body weight management and obesity prevention (Hartley, 2019).…”
Section: Discussionmentioning
confidence: 99%